INNOVATION MANAGEMENT IN THE CONDITIONS OF ECONOMIC CRISIS - Tastanbekova Karlygash Nyshanbaevna,; Sartova Rysty Bozmanaevna,; Bespalyy Sergey Vladimirovich,; Kusainov Halel Khaimullievich, (Academic Journal of Physical and Chemical Sciences, 2020)
There are many uncertainties in the innovative behavior of enterprises. The key role is played by the availability of sufficient financial resources, especially in the context of the financial and economic crisis; the interest of enterprises in direct budget support is increasing. At the same time, such restrictions as high cost of innovations, economic risk and long payback periods are maintained and even strengthened. A characteristic feature in the management of innovative activities of enterprises abroad is the persistent injection of funds, innovative development, as the main subject of economic growth in developed countries. Enterprises in the RK are aware of the insufficiency of their own innovative potential – the weakness of the research base, the lack of readiness to master the latest technological achievements, the lack of qualified personnel, and the lack of cooperation ties. They lack information on new technologies and potential markets for innovative products. Moreover, as a positive in terms of the potential growth of innovation, activity, one should assess the tendency to increase the interest of enterprises in obtaining information about new technologies. In this connection, the authors propose the main methods of innovation management in a crisis.